Dampak Depresi Terhadap Intensitas Nyeri dan Disabilitas pada Pasien dengan Chronic Low Back Pain - Felicia, Ivana; Singh, Arwinder (Jurnal Kedokteran Meditek, 2025)
Introduction: Low back pain (LBP) is a common health issue experienced by nearly 80% of people throughout their lives. This condition often recurs and can become chronic low back pain (CLBP) if it lasts for more than 3 months, with a prevalence of approximately 23% and causing disability in about 11-12% of the population. CLBP is often associated with depression, which can worsen pain intensity, function, and patient recovery. Purpose: This study aims to analyze the relationship between depression and CLBP, as well as the factors that influence it. Methods: The study uses a cross-sectional analytical observation method with consecutive sampling of 170 respondents. Data were collected through interviews and questionnaires, including pain intensity measurement using the Numeric Rating Scale, depression levels using the Beck Depression Inventory-II, and disability levels using the Oswestry Disability Index. Data collection was conducted at Sumber Waras Hospital and dr. Mintohardjo Naval Hospital. Results: The study results show the highest prevalence of LBP in individuals over 65 years old (47.65%), and the majority of respondents were female (70.59%). There is a significant relationship between pain intensity and depression (p < 0.001) and between disability and depression (p < 0.001). Pain duration was not significantly associated with depression (p = 0.211). Conclusion: In conclusion, pain intensity and disability level are significantly associated with the incidence of depression in CLBP patients.